1980
DOI: 10.1073/pnas.77.1.609
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an important physiological role for calcitonin

Abstract: We propose that calcitonin, secreted in response to the intake of food, aids in routing calcium, obtained by intestinal absorption, into bone fluid. Here calcium is temporarily stored in combination with phosphate for return to the extracellular fluid (blood) during intervals between oral intakes of calcium. The net result is a conservation of calcium postprandially and a decrease in parathyroid hormone-induced bone destruction during subsequent fasting periods. Evidence for this postulate is provided in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…These aggregates were distributed throughout the space separating bone lining cells from the mineralized bone surfaces. A similar dense material has been reported in tissue from calcitonin-injected postpartum rats [9], and from bone of normal fasted adult rats injected with calcitonin [5]. In the first report, the aggregates were stained with lanthanum.…”
Section: Calcium Removed From Tibia Washed In Weak Acidsupporting
confidence: 50%
See 2 more Smart Citations
“…These aggregates were distributed throughout the space separating bone lining cells from the mineralized bone surfaces. A similar dense material has been reported in tissue from calcitonin-injected postpartum rats [9], and from bone of normal fasted adult rats injected with calcitonin [5]. In the first report, the aggregates were stained with lanthanum.…”
Section: Calcium Removed From Tibia Washed In Weak Acidsupporting
confidence: 50%
“…This study now increases to four the different histological techniques that have identified bone fluid changes occurring only in or intensified by the presence of calcitonin. The two previously reported techniques [5,9] resulted from exogenous calcitonin administration and the two in this report were identified postprandially in TI rats and TX rats injected with calcitonin. Although the four methods all indicate that changes occurred in bone fluid, including the surfaces of bone, there were differences in the form and location of the calcitonin-stimulated material.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This hormone has a transient inhibitory effect on bone resorption, causing a temporary decrease in blood calcium levels (Van Noorden et al, 1977;Young and Leblond, 1963;Stux et al, 1961). The major effect of CT appears to be protection of the skeleton from excessive calcium losses, but its physiological function is still unclear (Zaidi et al, 1788;Van Der Wiel and Talmage, 1981;Talmage et al, 1980;Taylor et al, 1977). Despite the fact that the effects of the hormone have been studied intensively for more than 30 years, no syndrome in humans can be attributed either to its overproduction or its def-icit (Body, 1993;Tzanela et al, 1993;Tiegs et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was assumed that CT had an important role in the proper utilization of dietary calcium [4], However, most data had been ob tained with poorly sensitive and specific radioimmunoas says. The lack of sensitivity precluded definition of sub normal values and thus made very difficult the study of possible CT-deficiency conditions.…”
mentioning
confidence: 99%